2013
DOI: 10.1111/jocs.12260
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk, and Prevention of Ventilator-Associated Pneumonia in Adult Cardiac Surgical Patients: A Systematic Review

Abstract: Ventilator-associated pneumonia remains a major cause of morbidity and mortality in postoperative heart surgery patients. We present a systematic review of the literature on the incidence, risk factors, and prevention of this condition in a population at heightened risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
(91 reference statements)
7
19
0
3
Order By: Relevance
“…65,68 It was observed that in the case-control studies, the most prevalent extrinsic RF was IMV, 40,69,70 followed by previous hospitalization, 35,39 hospitalization time, 71 low McCabe score at admission, 34 gastrostomy or central line-associated bloodstream infection at admission, 34 recent surgery, 34 acute graft rejection, 38 urologic surgery, 35 antacid use, 33 recent exposure to piperacillin-tazobactam, 72 antibiotic use within the last 3 months, 35 prolonged steroid use, 36,39 orotracheal intubation, 70 catheter use ≥7 days, 73 aspiration of secretions, 70 and high Abbreviated Burn Severity Index score. 41 In the SRs, the most commonly mentioned extrinsic RFs were corticosteroid use, [42][43][44] IMV, 42,43,74 blood transfusion, 42,45,74 elective surgery, 43,45 CVC, 43,44 total parenteral nutrition 43,45 and abdominal surgery, 44,45 among others.…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%
“…65,68 It was observed that in the case-control studies, the most prevalent extrinsic RF was IMV, 40,69,70 followed by previous hospitalization, 35,39 hospitalization time, 71 low McCabe score at admission, 34 gastrostomy or central line-associated bloodstream infection at admission, 34 recent surgery, 34 acute graft rejection, 38 urologic surgery, 35 antacid use, 33 recent exposure to piperacillin-tazobactam, 72 antibiotic use within the last 3 months, 35 prolonged steroid use, 36,39 orotracheal intubation, 70 catheter use ≥7 days, 73 aspiration of secretions, 70 and high Abbreviated Burn Severity Index score. 41 In the SRs, the most commonly mentioned extrinsic RFs were corticosteroid use, [42][43][44] IMV, 42,43,74 blood transfusion, 42,45,74 elective surgery, 43,45 CVC, 43,44 total parenteral nutrition 43,45 and abdominal surgery, 44,45 among others.…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%
“…However, the incidence of VAP has been defined somewhat differently from study to study; there is currently no consensus on a common numerator or denominator that represents the overall incidence of VAP on a uniform basis. Commonly reported estimates include the percentage of patients on mechanical ventilation who develop VAP (cumulative incidence) and the number of VAP episodes per 1000 ventilator-days and VAP patients per 1000 ventilator-days [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increasing amount of literature on the risk factors of VAP [16][17][18][19] Moreover, the risk factors have been further confirmed in several meta-analyses. However, some stu dies focused on risk factors of VAP in neonates, while others focused on the incidence rates, risk f actors and outcomes of VAP in special ICUs, which may have excluded some data from integrated intensive care units (IICUs) and general ICUs [5,20].As such, we systematically reviewed the incide nce rates, risk factors and mortality rates of VAP patients in general ICUs or IICUs to provide evi dence for the clinical prevention of VAP.…”
Section: Introductionmentioning
confidence: 94%